IoT-based home control system using NodeMCU and Firebase - Paul Oluwatobiloba Ayeni; Olayiwola Charles Adesoba (Journal of Edge Computing, 2024)
Integrating Internet of Things (IoT) technology in home control systems has led to a significant advancement in the control and monitoring of home appliances and environmental conditions. This study presents the development of an IoT-based home control system that uses the NodeMCU ESP8266 microcontroller to manage several home appliances. This system connects to a Firebase real-time database to store or retrieve data in real-time. The user interacts with the IoT system through a mobile application named My Home, developed using Java programming language, and this mobile application is also interfaced with the Firebase cloud server. The developed IoT system allows users to control home appliances such as lights, sockets, fans, and cookers, and it also provides real-time updates of environmental parameters, such as temperature and humidity, which are measured by a DHT11 sensor. In addition, a PIR motion sensor was integrated into the system to enhance the home's security by detecting intrusion. The system's hardware functionality is based on a written Arduino code, which establishes Wi-Fi connectivity to a predefined network, communicates with the Firebase database, handles appliance control and manages sensor data. This IoT-based home control system shows the potential of integrating microcontrollers with cloud services to create a smart, responsive and user-friendly home control platform. The developed IoT system offers a foundation for advancements, thereby making it a valuable contribution to the growing field of smart home technology.